2010
DOI: 10.1007/s12663-010-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Bifid mandibular condyle: a study of the clinical features, patterns and morphological variations using CT scans

Abstract: Bifid Mandibular Condyle (BMC) are usually diagnosed on routine radiographic examination, is described in the literature as a rare entity. It is reported that BMC has no predilection by sex or ethnic background or the age. The etiopathogenesis of BMC still remains controversial and proper description of the condition is not defined owing to fewer reported cases. Dental professionals should have some knowledge of this anatomic abnormality, as well as its implications for function and appropriate treatment modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
11
0
2
Order By: Relevance
“…Nevertheless, mediolateral BMC after a condylar sagittal fracture have been described ( 8 , 11 , 15 ). Studies published by Balaji and Sampaio reported cases with mediolateral position and history of trauma ( 16 , 33 ). This study found that the 55.5% of condyles with an anteroposterior orientation and the 44.7% with a mediolateral position had history of trauma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, mediolateral BMC after a condylar sagittal fracture have been described ( 8 , 11 , 15 ). Studies published by Balaji and Sampaio reported cases with mediolateral position and history of trauma ( 16 , 33 ). This study found that the 55.5% of condyles with an anteroposterior orientation and the 44.7% with a mediolateral position had history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some cases have been diagnosed posteriorly as PAN did show no signs of pathology ( 22 , 33 ). CT is considered as the test of choice ( 13 , 16 , 18 , 30 , 32 ). Not only provides more information about condylar morphology but also helps to perform differential diagnosis with tumors and primary osseous cysts, metastatic lesions, degenerative bony lesions and metabolic lesions that could also alter the morphology ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these changes there was evidence of bifi dness of the condyles. Factors that lead to bifi d condyle are birth injury, trauma, or endocrine disorders [9]. In presented cases none of the factors leading to bifi d condyle were present.…”
Section: Discussionmentioning
confidence: 65%